2021
DOI: 10.1002/nau.24707
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent urinary tract infection: Association of clinical profiles with urobiome composition in women

Abstract: Aims: Clinical profiles of women with recurrent urinary tract infection (RUTI) are correlated with their urinary microbes. Methods: This IRB-approved, cross-sectional study enrolled adult women with RUTI. Urine samples (catheterized and voided) underwent culture by expanded quantitative urine culture (EQUC) and standard urine culture (SUC) methods. A validated symptom questionnaire, relevant clinical variables, and EQUC were used to identify symptom clusters and detect associations with specific urinary microb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
13
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 32 publications
2
13
1
Order By: Relevance
“…A decade after bacterial 16S rRNA gene sequences were detected in female urine samples [ 5 ] and live microorganisms were cultured using extended quantitative urine culture (EQUC) from samples classified as negative by standard urinary culture techniques [ 6 ], the existence of human urinary microbiota (UM) is now widely accepted. Changes in the UM have been observed in association with bladder dysfunction caused by spinal cord injury [ 7 ], lower urinary tract symptoms (LUTS) associated with benign prostatic hyperplasia [ 8 ], clinical profiles of LUTS in female recurrent urinary tract infections [ 9 ], painful conditions of the urinary bladder known as interstitial cystitis [ 10 ] and chronic prostatitis/chronic pelvic pain syndrome [ 11 ] and even bladder cancer [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…A decade after bacterial 16S rRNA gene sequences were detected in female urine samples [ 5 ] and live microorganisms were cultured using extended quantitative urine culture (EQUC) from samples classified as negative by standard urinary culture techniques [ 6 ], the existence of human urinary microbiota (UM) is now widely accepted. Changes in the UM have been observed in association with bladder dysfunction caused by spinal cord injury [ 7 ], lower urinary tract symptoms (LUTS) associated with benign prostatic hyperplasia [ 8 ], clinical profiles of LUTS in female recurrent urinary tract infections [ 9 ], painful conditions of the urinary bladder known as interstitial cystitis [ 10 ] and chronic prostatitis/chronic pelvic pain syndrome [ 11 ] and even bladder cancer [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Both, expanded urinary culture and 16S rRNA gene sequencing have proven that a microbial community exists in the bladder of healthy women [4][5][6][7][8][9][10]. Consequently, some studies have started to investigate its role in certain urogenital conditions [11][12][13]. Yet, knowledge about physiological attributes of urinary microbiota as a prerequisite for studying specific alterations and dynamics associated with diseases is still limited [14].…”
Section: Introductionmentioning
confidence: 99%
“… McDonald et al (2017) showed that 100% of symptomatic patients with UTI had NGS positive test results for urinary bacteria, compared with a positive rate of 30% in SUC. Burnett et al (2021) found that expanded quantitative urine culture (EQUC) could detect more urinary microbes than SUC, and their urobiome compositions were associated with distinct clinical profiles in patients with RUTI. Hochstedler et al (2022) showed that EQUC detected more uropathogens than SUC from catheterized and voided urine in patients with RUTI.…”
Section: Introductionmentioning
confidence: 99%